Canadian International Petroleum Conference 2005
DOI: 10.2118/2005-015
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Asphaltene Precipitation in an Iranian South Oil Field

Abstract: Asphaltene deposit formation is a severe problem frequently faced during crude oil production that affects the reservoir, production tubing and facilities, depending on the stage where this critical point is reached. This point corresponds to the pressure at which asphaltene particles start to form and directly related to the oil chemical physical stability.Modeling of asphaltene precipitation in the reservoir porous media and in the oilwell tubing of an Iranian south oil field is the purpose of this study. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…But in the literature, two proposed structures define the asphaltene molecules as presented in figure 1: the continental (large central aromatic region with small alkyl chains on the periphery) and the archipelago models (smaller aromatic regions linked by bridging alkanes) [37]. On heating, they are not melted but decompose, forming carbon and volatile products above 300 to 400 o C [6,18,38]. On heating, they are not melted but decompose, forming carbon and volatile products above 300 to 400 o C [6,18,38].…”
Section: Structure Of Asphaltenementioning
confidence: 99%
See 2 more Smart Citations
“…But in the literature, two proposed structures define the asphaltene molecules as presented in figure 1: the continental (large central aromatic region with small alkyl chains on the periphery) and the archipelago models (smaller aromatic regions linked by bridging alkanes) [37]. On heating, they are not melted but decompose, forming carbon and volatile products above 300 to 400 o C [6,18,38]. On heating, they are not melted but decompose, forming carbon and volatile products above 300 to 400 o C [6,18,38].…”
Section: Structure Of Asphaltenementioning
confidence: 99%
“…Published data records the molecular weight of Asphaltene in the range of 500 to 500000 [6,36]. Due to the natural tendency of asphaltene molecules to aggregate, the true molecular weight determination is very difficult and takes too much effort.…”
Section: Molecular Weight Of Asphaltenementioning
confidence: 99%
See 1 more Smart Citation
“…32 Recently, it was reported that Daedaleopsis sp, isolated from wood-degrading fungi, can degrade asphaltene fraction and dibenzofuran, and in comparison with available studies, this strain could consume more asphaltenes and 88.7% asphaltene biodegradation in crude oil could be attached by this microorganism after 14 days of incubation at 40 °C and pH = 5. 33 The asphaltene precipitation phenomenon in the oil equipment is a serious challenge in the production facilities in the Iranian southwest oilfields, 34,35 and the previous reports showed that there is not a comprehensive study on the possibility of biodegradation of precipitated asphaltenes that considers all culture medium parameters in operational condition and isolated indigenous bacteria from available oilcontaminated samples. Asphaltene biodegradation is a timeconsuming process, and a comprehensive studies on microorganisms' population in the oilfields is required.…”
Section: Introductionmentioning
confidence: 99%
“…The asphaltene precipitation phenomenon in the oil equipment is a serious challenge in the production facilities in the Iranian southwest oilfields, , and the previous reports showed that there is not a comprehensive study on the possibility of biodegradation of precipitated asphaltenes that considers all culture medium parameters in operational condition and isolated indigenous bacteria from available oil-contaminated samples. Asphaltene biodegradation is a time-consuming process, and a comprehensive studies on microorganisms’ population in the oilfields is required.…”
Section: Introductionmentioning
confidence: 99%